ANTHROPOGENIC FACTORS OF THE MORPHOGENESIS OF THE ARID ZONE OF KAZAKHSTAN (CENTRAL KAZAKHSTAN) (Journal of Geography and Environmental Management, 2018)
In article the major anthropogenic factors, defining spatial distribution and dynamics of negativeprocesses of a morphogenesis within a platform-denudational plains of the Central Kazakhstan which arecharacterized by aridity of climatic conditions are considered. Changes of processes of a morphogenesisand components of the environment is defined by type (engineering and economic, mining and miningprocessing industries, agricultural, town-planning, etc.) and character (direct and mediated) economicinfluence. The lands broken by economic activity occupy the huge spaces, catastrophically reducing territoriesof the equipped vital space of the population of the Central Kazakhstan.